AKIBAT HUKUM BAGI PELAKU PENYEBARAN INFORMASI PALSU (HOAX) BERDASARKAN UU ITE - Prasetyo Wibowo, Dedi; Sudarto (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
This research examines the legal consequences for perpetrators of spreading false information (hoaxes) based on the Electronic Information and Transactions Law (ITE Law) in Indonesia. The phenomenon of spreading hoaxes has become a serious problem in the digital era, causing unrest and potential conflict in society. The ITE Law is the main instrument in the government's efforts to deal with hoax cases in the digital realm. This study analyses the provisions of the ITE Law that regulate the dissemination of false information, particularly Article 28 paragraphs (1) and (2) and Article 45A. The results show that perpetrators of spreading hoaxes can be subject to criminal sanctions in the form of imprisonment for a maximum of 6 years and/or a fine of up to 1 billion rupiah. However, the application of this law still faces challenges, including a vague definition of hoax, difficulty in proving the element of intent, and concerns over restrictions on freedom of expression. The study also identifies inconsistencies in court decisions related to hoax cases, leading to a debate on the balance between combating hoaxes and protecting fundamental rights. The study concludes that while the ITE Law provides a strong legal basis for cracking down on perpetrators of hoaxes, regulatory improvements and a more comprehensive approach are needed to address the complexity of this issue in the digital age.